Community Readiness in Emergency First Aid for Victims of Traffic Accidents - Kuzzairi; cantika iva nugrahani; Moh. Fityan Arrofiqi (PROFESSIONAL HEALTH JOURNAL, 2024)
A traffic accident is an emergency condition that requires immediate or life-threatening help. It is important for all people to have readiness regarding initial handling/first aid quickly and precisely so that the chain of handling traffic accident victims can run properly and correctly. This research aims to find out how the level of community readiness for emergency first aid for victims of traffic accidents on Jalan Raya Gapura, Sumenep Regency. This study uses a descriptive design. The population and sample of this study, namely the entire community along the edge of Jalan Raya Gapura, Braji Village, Sumenep Regency, consisting of 30 people, used a non-probability sampling technique - total sampling. The research instrument used a Type Multiple Choice Questionnaire with 10 questions. The results of the data are processed by means of editing, coding, scoring, tabulating. Nearly half of the respondents were in the unprepared category 14 (47%), almost half of the respondents were in the quite ready category 10 (33%), and a small proportion of respondents were in the ready category 6 (20%). Based on the results of the study, it was found that most of the community's readiness level for emergency first aid for victims of traffic accidents on Jalan Raya Gapura, Sumenep Regency, was with a less prepared level of readiness.